2022
DOI: 10.1016/j.japh.2021.11.028
|View full text |Cite
|
Sign up to set email alerts
|

A social media microinfluencer intervention to reduce coronavirus disease 2019 vaccine hesitancy in underserved Tennessee communities: A protocol paper

Abstract: Background: Central to effective public health policy and practice is the trust between the population served and the governmental body leading health efforts, but that trust has eroded in the years preceding the pandemic. Vaccine hesitancy among adults is also a growing concern across the United States. Recent data suggest that the trustworthiness of information about the coronavirus 2019 (COVID-19) vaccine was a larger concern than the vaccine's adverse effects or risks.Objective: This study aims to describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
(44 reference statements)
0
4
1
Order By: Relevance
“…The other two components of vaccination confidence, namely vaccine effectiveness and side effects (safety), show no correlation with the information sources. This contradicts the findings of Hohmeier et al [ 55 ] and Huang [ 47 ], who purport that personal network exposure (community physicians, community pharmacists, and community opinion leaders) signifies a positive impact on vaccine effectiveness and safety. Furthermore, this study finds that trust in vaccine approval by the government relates to parents’ perceived efficacy and side effects (safety), and is very likely to increase the overall acceptability rate of pediatric vaccination.…”
Section: Discussioncontrasting
confidence: 73%
“…The other two components of vaccination confidence, namely vaccine effectiveness and side effects (safety), show no correlation with the information sources. This contradicts the findings of Hohmeier et al [ 55 ] and Huang [ 47 ], who purport that personal network exposure (community physicians, community pharmacists, and community opinion leaders) signifies a positive impact on vaccine effectiveness and safety. Furthermore, this study finds that trust in vaccine approval by the government relates to parents’ perceived efficacy and side effects (safety), and is very likely to increase the overall acceptability rate of pediatric vaccination.…”
Section: Discussioncontrasting
confidence: 73%
“…On another positive note, our work adds to the growing evidence 49,50 that that microinfluencer-based public health messaging is an impactful intervention for enabling health seeking behaviour, in this case amongst younger people most impacted by altered radon exposure due to shifted activity patterns. Our microinfluencer case study observed large gains in radon awareness and testing achieved using this technique, and we developed tools (i.e., the interaction index) that may prove useful by public health communicators seeking to motivate behaviour change in younger people.…”
Section: Discussionmentioning
confidence: 69%
“…Microinfluencers are non-traditional, often local celebrities with between 5000 and 50,000 social media subscribers that demonstrate high degrees of trust (in the influencer) via parasocial interactions and relationships 48 . Microinfluencer marketing has been found to be effective in the context of tobacco reduction for younger people 49 and, most recently, vaccine hesitancy among under-served USA populations 50 , but systematic evaluation in the context of public health messaging remains limited. Ten Instagram microinfluencers located in the Canadian province of Alberta were hired in spring and summer of 2021 to deliver at least three curated posts describing radon health effects, what radon testing involved, and how to interpret test outcomes for their own properties (see Supplemental Information, Section II).…”
Section: An Intervention To Encourage Health-seeking Behaviour Amongs...mentioning
confidence: 99%
“…5 A variety of strategies to increase vaccine uptake have been utilized in rural communities across the nation, with varied results. 6 - 8 …”
Section: Introductionmentioning
confidence: 99%
“…5 A variety of strategies to increase vaccine uptake have been utilized in rural communities across the nation, with varied results. [6][7][8] Research has shown that rural populations are at significant risk for morbidity and mortality associated with COVID-19 due to factors that include age stratification, the high prevalence of elderly individuals, and pre-existing comorbidities such as heart disease, diabetes, obesity, and smoking status. [9][10][11] This, along with limited health care access, fewer life-saving resources including intensive care units and ventilators, and lower health literacy, put rural US communities at significant risk of COVID-19 related morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%